Lightning the future of education in Brazil : the impact of rural electrification on educational outcomes (2018)
In this document we analyze the impact of rural electricity access in Brazil on different educational outcomes for children. Namely, we study test scores (Prova SAEB for 5th and 9th graders), years of schooling, literacy rates, attendance rates and approval rates for 5th and 9th grade. To deal with endogeneity bias derived from non random extension of electricity projects and double causality we propose a Regression Discontinuity (RD) approach and use census data at the school and child level for 2010 and test score data for 2011. We take advantage of the Luz Para Todos (LPT) program priorization criteria to build an assignment variable that divides our sample and extracts the exogenous variation in rural electricity access during this period. We provide evidence that lying below the exogenous cutoff determined by the program has a positive and significant effect on test scores for both Language and Math in 5th and 9th grade. It also increases children?s likelihood of being literate by 8 pps, and similarly, schools in municipalities below the cutpoint have higher approval rates for 5th and 9th grade. We argument that the effect is driven by an increase in electricity access and use within schools which empirically remarks the importance of electrical device access and technology use on modern education.